2019
DOI: 10.1038/s41467-019-09168-z
|View full text |Cite
|
Sign up to set email alerts
|

Model states for a class of chiral topological order interfaces

Abstract: Interfaces between topologically distinct phases of matter reveal a remarkably rich phenomenology. To go beyond effective field theories, we study the prototypical example of such an interface between two Abelian states, namely the Laughlin and Halperin states. Using matrix product states, we propose a family of model wavefunctions for the whole system including both bulks and the interface. We show through extensive numerical studies that it unveils both the universal properties of the system, such as the cen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 54 publications
2
53
0
Order By: Relevance
“…Indeed, entanglement entropy is a well-established probe of quantum matter and of gapless edge modes in particular, as was shown e.g. in 2D droplets [39,51], at interfaces between fractional quantum Hall states [52][53][54], or in 3D topological insulators with hinge modes [55,56]. Since we are dealing here with non-interacting fermions, calculations simplify considerably [40][41][42][43][44]: one can relate the entanglement spectrum to that of a subregion-restricted correlation matrix, reducing the computation of many-body entanglement to a one-body problem.…”
Section: Quantum Entanglementmentioning
confidence: 90%
“…Indeed, entanglement entropy is a well-established probe of quantum matter and of gapless edge modes in particular, as was shown e.g. in 2D droplets [39,51], at interfaces between fractional quantum Hall states [52][53][54], or in 3D topological insulators with hinge modes [55,56]. Since we are dealing here with non-interacting fermions, calculations simplify considerably [40][41][42][43][44]: one can relate the entanglement spectrum to that of a subregion-restricted correlation matrix, reducing the computation of many-body entanglement to a one-body problem.…”
Section: Quantum Entanglementmentioning
confidence: 90%
“…We have also put the bosonic model (m = 2) discussed in Ref. [29] under scrutiny of finite size ED. The results that we have obtained underline the microscopic validity of the model state and its applicability to both fermions and bosons.…”
Section: Data Availabilitymentioning
confidence: 99%
“…While powerful, these effective field theory approaches suffer from a complete lack of connection with a more physical, microscopic description. In order to overcome this limitation we have recently proposed a family of Matrix Product State (MPS) model wavefunctions for the Laughlin-Halperin interface capable of describing the whole system including both bulks and the interface [29]. We found that these MPSs faithfully describe the bulks intrinsic topological order while presenting the expected universal low-energy physics at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…in Camino et al's interferometric experiments which aimed at demonstrating the fractional statistics [21]. There are also some proposals for creating interfaces with a non-Abelian state on at least one side [11,22,23].…”
Section: Introductionmentioning
confidence: 99%